Perbedaan Perilaku Konsumtif Berdasarkan Jenis Kelamin pada Penggemar KPOP NCT - Azzahra, Latifah Pratiwi; Adiba, Nazila Faradhila; Wulandari, Devi (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2025)
South Korean pop culture or better known as K-pop has captured the attention of the world, including Indonesia. One of them is NCT, a K-pop group that has 69 types of official merchandise including albums and clothes, with prices ranging up to millions of rupiah. The purpose of this study was to observe differences in consumptive behavior based on gender among NCT K-Pop fans. The design used in this study is a Cross Sectional research design, with a sampling technique that is Non-Probability Sampling with 75 female respondents, and 75 male respondents who filled out the Consumptive Behavior Scale questionnaire. The results showed that there were differences in consumptive behavior between male and female K-Pop NCT fans, t (148) = 9.221. Female K-Pop NCT fans (M = 79.52) tend to be more consumptive than men (M = 64.03).